2006
DOI: 10.1016/j.physletb.2006.03.051
|View full text |Cite
|
Sign up to set email alerts
|

Influence of projectile α-breakup threshold on complete fusion

Abstract: Complete fusion excitation functions for 11,10 B+ 159 Tb have been measured at energies around the respective Coulomb barriers, and the existing complete fusion measurements for 7 Li+ 159 Tb have been extended to higher energies. The measurements show significant reduction of complete fusion cross sections at above-barrier energies for both the reactions, 10 B+ 159 Tb and 7 Li+ 159 Tb, when compared to those for 11 B+ 159 Tb. The comparison shows that the extent of suppression of complete fusion cross sections… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
129
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(141 citation statements)
references
References 35 publications
12
129
0
Order By: Relevance
“…There is no suppression in TF cross sections in above barrier region with respect to the theoretical predictions. This observation agrees with the earlier observations from all the weakly bound stable projectiles, that the TF cross sections are unaffected by the breakup of projectile irrespective of target mass [4][5][6][7]10,[12][13][14][15]. But the observed subbarrier enhancement of TF cross sections is not understood clearly.…”
supporting
confidence: 87%
See 3 more Smart Citations
“…There is no suppression in TF cross sections in above barrier region with respect to the theoretical predictions. This observation agrees with the earlier observations from all the weakly bound stable projectiles, that the TF cross sections are unaffected by the breakup of projectile irrespective of target mass [4][5][6][7]10,[12][13][14][15]. But the observed subbarrier enhancement of TF cross sections is not understood clearly.…”
supporting
confidence: 87%
“…In case of fusion of weakly bound stable projectiles like, 6 Li (S α = 1.47 MeV), 7 Li (S α = 2.47 MeV) and 9 Be (S n =1.67 MeV), two principal observations are: the suppression of complete fusion (CF) cross section with respect to one dimensional barrier penetration model (1DBPM) prediction at the above barrier energies and the enhancement of fusion cross section at below barrier energies [3][4][5][6][7][8][9][10][11][12]. While, the suppression at above barrier energies received maximum attention in the study of fusion of weakly bound systems, the subbarrier enhancement of fusion cross section of these systems is also equally important to understand the interplay of reaction mechanisms in this energy regime.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Using the experimentally determined average barrier energy, it was shown that above-barrier complete fusion cross-sections of the weakly-bound nucleus 9 Be + 208 Pb is suppressed [2] compared with the expectations of well bound nuclei. Complete fusion suppression has since been seen in many reactions with weakly bound stable nuclei [3][4][5][6][7][8][9]. However, studies on medium-mass and light target nuclei are sparse as experimentally it is difficult to separate complete fusion (experimentally defined as capture of the full charge of the projectile) from incomplete fusion (only part of the projectile charge is captured).…”
mentioning
confidence: 99%